2009
DOI: 10.1089/end.2008.0630
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Difference Between Percutaneous Nephrolithotomy in Patients with and without Previous Open Renal Surgery?

Abstract: PCNL in patients who previously underwent open renal surgery is effective and safe. We found no difference in results between the two groups based on the number of stones and the number of accesses. The step 1 of dilatation was the only difference between the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 14 publications
6
16
0
2
Order By: Relevance
“…Also Onal's study supported our findings [27]. As distinct from our study, Falahatkar's study had a higher fever rate as 33.3 % in patient with previous open renal surgery and 26.5 % without [28]. Sofikerim et al faced 11 and 9.7 % fever in patients with and without open renal surgery, respectively [16].…”
Section: Discussionsupporting
confidence: 84%
“…Also Onal's study supported our findings [27]. As distinct from our study, Falahatkar's study had a higher fever rate as 33.3 % in patient with previous open renal surgery and 26.5 % without [28]. Sofikerim et al faced 11 and 9.7 % fever in patients with and without open renal surgery, respectively [16].…”
Section: Discussionsupporting
confidence: 84%
“…9 Complete stone clearance was achieved in 96.7% of patients in the study group and 93.3% patients in the control group. Similar result was seen in studies of Shah et al 10 and Falahatkar et al 7 Khan et al, Falahatkar et al, Gupta et al and Resorlu et al in their studies reported that previous open stone surgery does not alter the outcome of subsequent PCNL signi cantly. 6,7,8,11 In the present study it was found that there is no di erence in outcome of PCNL between the two groups based on the previous open renal surgery and primary patients without previous renal surgery.…”
Section: Resultssupporting
confidence: 86%
“…Falahatkar et al in a study showed that the mean postoperative hospital stay was 85.88±17.25 hours and 80.20±17.71 hours in the group of previous surgery and in the group of no previous surgery, respectively that results were similar to our result. 7 Gupta et al reported that the hospital stay was similar in both groups. 8 Kurtulus et al in a similar study found no signi cant di erence in hospitalization time (4.4 v 4.2 days).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Sofikerim et al and Falahatkar et al reported 33.3% and 11% fever rates, repectively, in their patients with previous ORSS. 12,13 Sterile urine cultures were obtained from every patient prior to surgery. Additionally, we finalzed the PNL procedure if purulent urine discharge was observed from the nephrostomy tract, which may explain our lower fever rates.…”
Section: Discussionmentioning
confidence: 99%